COMPETITIVE MSME STRATEGY: BUSINESS WORKSHOP, HALAL CERTIFICATION, AND DIGITALIZATION IN KEMASANTANI VILLAGE - Mujahada , Darda; Agung Saputra , Alfiansyah; Aisah Putri, Sabrina; Dinda Amalia Kartika , Tiara; Harsono, Budwi (Journal of Social Comunity Services, 2025)
Objective: Micro, Small, and Medium Enterprises (MSMEs) significantly contribute to economic growth, employment, and community welfare. However, they face persistent challenges in marketing, legality, and technological adaptation. This study aims to enhance the competitiveness of MSMEs in Kemasantani Village through structured interventions, including business workshops, halal certification assistance, and digitalization strategies. Method: A participatory approach was employed, involving direct engagement with MSME actors. Training sessions were conducted on digital marketing, guided assistance was provided for halal certification, and digital platforms were introduced to optimize business operations. Results: The intervention yielded significant outcomes, with 85% of participants demonstrating an improved understanding of digital marketing, 15 MSMEs successfully obtaining halal certification, and 60% of participants recognizing the potential of the digital market for business expansion. Novelty: This study provides an integrated model of MSME development by combining digital literacy, legal compliance, and market expansion strategies. The findings highlight the effectiveness of a participatory approach in empowering MSMEs, offering a scalable framework for enhancing business sustainability and competitiveness in similar rural contexts.